MENTAL HEALTH SUPPORT STRATEGIES IN THE WORKPLACE: ASSESSING THEIR IMPACT ON EMPLOYEE WELL- BEING AND PRODUCTIVITY - Dewi, Dyah Handayani (Penelitian dan Pengembangan Ilmu, 2024)
This research examines the influence of mental health support strategies on employee productivity in various industrial sectors. The main aim of this research is to explore various mental health programs, such as psychological counseling, stress management training, and work-life balance policies, and their impact on increasing productivity. The method used was a systematic review of 50 studies published between 2014-2024. Research results show that implementing mental health programs can increase employee productivity by 15-25%, with proactive strategies proving to be more effective than reactive strategies. The implications of this research show the importance of integrating mental health programs in organizational policies to improve employee well-being and business performance.